The spatio-temporal dynamics of mitochondrial membrane potential during oocyte maturation - AL-Zubaidi, Usama; Liu, Jun; Cinar, Ozgur; Robker, Rebecca L; Adhikari, Deepak; Carroll, John (Molecular human reproduction, 2019)
Mitochondria are highly dynamic organelles and their distribution, structure and activity affect a wide range of cellular functions. Mitochondrial membrane potential (∆Ψm) is an indicator of mitochondrial activity and plays a major role in ATP production, redox balance, signaling and metabolism. Despite the absolute reliance of oocyte and early embryo development on mitochondrial function, there is little known about the spatial and temporal aspects of ΔΨm during oocyte maturation. The one exception is that previous findings using a ΔΨm indicator, JC-1, report that mitochondria in the cortex show a preferentially increased ΔΨm, relative to the rest of the cytoplasm. Using live-cell imaging and a new ratiometric approach for measuring ΔΨm in mouse oocytes, we find that ΔΨm increases through the time course of oocyte maturation and that mitochondria in the vicinity of the first meiotic spindle show an increase in ΔΨm, compared to other regions of the cytoplasm. We find no evidence for an elevated ΔΨm in the oocyte cortex. These findings suggest that mitochondrial activity is adaptive and responsive to the events of oocyte maturation at both a global and local level. In conclusion, we have provided a new approach to reliably measure ΔΨm that has shed new light onto the spatio-temporal regulation of mitochondrial function in oocytes and early embryos.